Adsorption of Abattoir Wastewater Contaminants by Coconut Shell-Activated Carbon - Lawal I.M.; Soja U.B.; Mambo A.D.; Kutty S.R.M.; Jagaba A.H.; Hayder G.; Abubakar S.; Umaru I. (Springer Nature, 2024)
Abattoir wastewater composition depends on type and number of animals slaughtered, as well as the processs water requirements. As a result, it must be treated before being discharged in order to preserve the environment. The utilization and efficacy of activated coconut shell derived from agricultural waste for the removal of some recalcitrant target contaminants in abattoir wastewater were explored in this study. The use of this adsorbent as a potential replacement for advanced treatment methods was examined in a batch test. The maximum adsorption capacity was determined by varying adsorbent dosages at 25, 30, 35, 40, 45 and 50g and at reaction time of 24, 48, 72, 96 and 120hr. At 24hr contact time, the pH ranged between 6.7 and 8.0. The optimum dosage, reaction time and percentage removal of electrical conductivity (30g/l, 120hr, 56.57%), ammonia (50g/l, 48hr, 61.55%), colour (50g/l, 120hr, 78.6%), total suspended solid (45g/l, 24hr, 26.64%) and chemical oxygen demand (50g/l, 24hr, 73.28%), respectively. From the results obtained, adsorption efficiency improved as adsorbent dosage was increased albeit at different reaction time. Hence, low-cost adsorbent such as coconut shell can be used as an alternative and cost-effective treatment technique for abattoir wastewater for a safe disposal. 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.